Effectiveness of modern dressing in wound care for breast cancer patients: A systematic review - Joni Siahaan; Dessy Syahfitri Pohan; Zulaika Harissya; Armi Armi; Yana Setiawan; Kharina Nurshadrina; Primaloya Septiavy Estiadewi (Science Center Group, 2026)
Background: Breast cancer patients frequently experience wound complications following surgery, radiotherapy, or disease progression, which may negatively affect healing outcomes, comfort, and quality of life. Modern dressing technologies have been developed to improve wound management through antimicrobial, hemostatic, protective, and moisture-balancing properties. Objective: This systematic review aimed to evaluate the effectiveness of modern dressings in wound care for breast cancer patients by synthesizing current clinical evidence on infection prevention, radiation dermatitis control, bleeding management, symptom relief, and patient-centered outcomes. Methods: This study employed a systematic literature review design following the PRISMA 2020 guidelines. A comprehensive search was conducted in PubMed, Scopus, ScienceDirect, ProQuest, and Google Scholar for studies published between 2013 and 2023 in English and Indonesian. Eligible studies included randomized controlled trials, quasi-experimental, and prospective clinical studies examining modern dressing or topical interventions in breast cancer wound care. Data extraction and risk of bias assessment were performed independently by two reviewers, and findings were synthesized narratively due to methodological heterogeneity. Results: Eleven studies met the inclusion criteria. Modern dressings demonstrated effectiveness in reducing surgical site infections, minimizing radiation dermatitis severity, controlling bleeding and exudate, reducing bacterial colonization, and improving patient comfort. Several interventions also showed positive effects on wound malodor reduction and quality of life improvement. Overall findings suggest that modern dressings provide multidimensional benefits in clinical and psychosocial aspects of wound management in breast cancer patients. Conclusion: Modern dressing strategies represent effective interventions for improving wound healing outcomes and patient well-being in breast cancer care. Integration of evidence-based dressing technologies into clinical practice may enhance both physiological recovery and holistic patient comfort, although further high-quality research is recommended to strengthen clinical guidelines.